Differences in Health-Related Quality of Life of Adults with Cardiovascular or Metabolic Diseases Compared to the General Population - Yeunhee Kwak; Yoonjung kim (Tehran University of Medical Sciences, 2021)
Background: We aimed to compare demographic, health-related characteristics, and quality of life between adults with cardiovascular or metabolic diseases and the general population. Methods: Data from 25,712 adults assessed on the Korea National Health and Nutrition Examination Survey V & VI (2010-2013) were analyzed for differences in health-related quality of life. Results: The corrected EuroQol-5 Dimension score mean among participants with cardiovascular or metabolic diseases was significantly lower than for the general population across all five dimensions (P<0.001). Individuals with cardiovascular disease had lower quality of life than those with metabolic diseases. Conclusion: Adults with cardiovascular or metabolic diseases reported lower health-related quality of life in all domains when compared to adults in the general population. Therefore, interventions and management to improve quality of life among patients with cardiovascular or metabolic diseases are necessary.